Increased anxiety from fear of Omicron in China as compared to North America and Western Europe: A cross-sectional Kendall’s tau-b analysis using the generalized anxiety disorder 7-item questionnaire - Shan, Dan; Liu, Chang; Li, Shaoyang; Zheng, Yuandian (Frontiers in Psychiatry, 2022)
Background: Varying policies for handling the global pandemic in different countries have led to differences in public perceptions of the COVID-19, especially for people’s subjective attitudes toward the after-effects of the latest variant of COVID-19 - Omicron. Many unofficial Chinese media outlets frequently spread non-evidence-based information of COVID or greatly exaggerated rare sequelae of Omicron lacking common consent of systematic study for the sake of attention, leading Chinese people to panic situation, in comparison with the large shift in attitudes toward Omicron in other countries around the world, especially in North America and Western Europe. Objective: This article primarily aims to investigate the association between Chinese people's attitudes toward the potential after-effects of Omicron and their anxiety status, as compared to these of people living in North America or Western Europe. Methods: We conducted a questionnaire survey via the Credamo and collected data from 500 Chinese (not living in Shanghai), another 500 Chinese (living in Shanghai) and 500 people living in North America or Western Europe in June 2022. Results: The results suggested that subjective attitudes of Chinese participants toward the sequelae of Omicron were positively and significantly associated with their anxiety status (i.e., GAD-7 scores) in Shanghai (China) (Tb = 0.44, p< 0.01) and other parts of China outside Shanghai (Tb = 0.37, p< 0.01). However, no such significant correlation was found in North America & Western Europe (Tb = -0.01, p> 0.05). Conclusions: Our findings showed that Chinese participants who were more worried about the after-effects of Omicron had higher levels of anxiety. Although we still need to pay sufficient attention to COVID-19 and its long effects, we should take everything related to COVID-19 seriously based on the available scientific evidence, and not easily believe exaggerated or even false reports in the mass media. In the future, more relevant studies are needed to reveal the truly long-term impacts of Omicron or subsequent variants of COVID-19.